2016
DOI: 10.1016/j.bcmd.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of BCL11A and HMIP-2 polymorphisms on endogenous and hydroxyurea induced levels of fetal hemoglobin in sickle cell anemia patients from southern Brazil

Abstract: High levels of fetal hemoglobin (HbF) reduce sickle cell anemia (SCA) morbidity and mortality. HbF levels vary considerably and there is a strong genetic component that influences HbF production. Genetic polymorphisms at three quantitative trait loci (QTL): Xmn1-HBG2, HMIP-2 and BCL11A, have been shown to influence HbF levels and disease severity in SCA. Hydroxyurea (HU) is a drug that increases HbF. We investigated the influence of single nucleotide polymorphisms (SNPs) at the Xmn1-HBG2 (rs7482144); BCL11A (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…This SNP accounted for 13.4% of HbF variability among our Kurdish SCD patients. Similarly, this SNP was found to contribute significantly to HbF variability in several SCD populations including Indians (23%), Eastern Saudi Arabians (7.5%), Cameroonians (6.3%), Southern Brazilian, and African Americans …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This SNP accounted for 13.4% of HbF variability among our Kurdish SCD patients. Similarly, this SNP was found to contribute significantly to HbF variability in several SCD populations including Indians (23%), Eastern Saudi Arabians (7.5%), Cameroonians (6.3%), Southern Brazilian, and African Americans …”
Section: Discussionmentioning
confidence: 90%
“…In the present study, MAF of rs9399137 is 0.137, which is among the highest frequencies observed in SCD populations (Table ). This SNP has been reported to be associated with HbF levels in other populations, including Indian, African American, Cameroonian, Tanzanian, British, and Eastern and Southern Brazilian patients, but not in Saudi Arabian or North Brazilian SCD patients …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This was the case for Xmn1 in our cohort, which may have resulted from its rarity. A study comparing two cohorts of European and African origin observed differences in allele frequency and correlation with HbF [51]. Another study, conducted in Cameroon, showed identicallelic frequencies between a Cameroonian population and the African-American cohort, but a lower impact on HbF among Africans [52].…”
Section: Snps Is Associated With High Hb F Levelmentioning
confidence: 99%
“…These three loci account for approximately 20–50% of HbF variability in patients with SCA . To date, few works analyzed their associations with clinical and biological parameters but two major limitations could be highlighted: (1) the most severe patients with SCA received hydroxyurea (HU), a well‐known HbF inducer that may have blunted the effects of the HbF‐QTL and (2) no study focused on the differential effects of the HbF‐QTL according to the alpha‐thalassemia status.…”
Section: Introductionmentioning
confidence: 99%